Factors influencing the consumer purchase behavior / Dr. Sarah Sabir Ahmad, Dr. Azfahanee Zakaria and Dr. Mhd Azmin Mat Seman - Sabir Ahmad, Sarah; Zakaria, Azfahanee; Mat Seman, Mhd Azmin (Universiti Teknologi MARA, Kedah, 2023)
The information of buyers and the approaches they employ to choose, use, and discard goods and services, as well as the emotional, mental, and behavioral reactions of consumers, is known as consumer purchase behavior (Radu, 2019). Consumer purchase behavior is also known as the study of how people make decisions about what to buy in order to fulfil their needs, wants, or desires, as well as how those decisions are influenced by their emotions, thoughts, and behaviors (StudyCorgi, 2021). Understanding consumer purchase behavior is important as it assist businesses understand what influences the consumers’ purchase decision and how to present the ideas and products to the consumers. There are various factors that affect this decision and some of those factors are discussed in the next sections.